PENGARUH VARIABEL KEUANGAN DAN NON KEUANGAN TERHADAP UNDERPRICING PADA SAHAM PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - asih yuli astuti; syahyunan syahyunan (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT This research is aimed to determine and to analyze the effect of financial variables that consist of return on assets (ROA), debt to equity ratio (DER), the amount of the company (size), earnings per share (EPS), the size of stocks offering (proceeds) and non financial variables that consist of firm age, underwriter reputation, auditors reputation, inflation, and interest rates effect on underpricing of company stock doing Initial Public Offering (IPO) in Indonesia Stocks Exchange (January 2007 to June 2012). The analysis method that is used multiple linear regression analysis. The sample of this research is 67 companies. The results of this research is ROA, DER, the amount of the company (size), earnings per share, the size of the stock offering (proceeds), the age of the company, underwriter reputation, auditor reputation, inflation, and interest rates with significancy (α = 5%), simultaneously effect on underpricing. Partially, only underwriter reputation that significantly and negatively related to underpricing, while ROA, DER, the amount of the company (size), EPS, the size of the stock offering (proceeds), age of firm, auditor reputation, inflation, and interest rates didn’t significantly effect on underpricing of company stock doing Initial Public Offering (IPO) in Indonesia Stocks Exchange (January 2007 to June 2012). Key Word : return on asset, debt to equity ratio, the amount of the company (size), earning per share, the size of the stock offering (proceeds), the age of the company, underwriter reputation, the reputation of auditors, inflation, interest rates, and underpricing.